1991
DOI: 10.1128/mcb.11.1.338
|View full text |Cite
|
Sign up to set email alerts
|

Transient activity assays of the Trypanosoma brucei variant surface glycoprotein gene promoter: control of gene expression at the posttranscriptional level.

Abstract: The putative promoter of the variant surface glycoprotein (VSG) gene of Trypanosoma brucei was cloned into a plasmid containing the chloramphenicol acetyltransferase (CAT) gene. After electroporation into trypanosomes, this construct directed the expression of the CAT reporter gene. The essential region for promoter activity was found to reside within 88 bp upstream of the putative transcription start site. Transcription of the CAT construct occurred at approximately the same level in both bloodstream and proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
82
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(89 citation statements)
references
References 42 publications
(44 reference statements)
7
82
0
Order By: Relevance
“…Thus, VSG ESs are active when transfected as episomes in cells, indicating that several promoters can be active simultaneously (38). This conclusion is also true in procyclic forms, where the ES promoters are normally not active (38). The very simple structure and ribosomal nature of the ES promoters (39,40) is in keeping with the absence of regulatory sequences.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Thus, VSG ESs are active when transfected as episomes in cells, indicating that several promoters can be active simultaneously (38). This conclusion is also true in procyclic forms, where the ES promoters are normally not active (38). The very simple structure and ribosomal nature of the ES promoters (39,40) is in keeping with the absence of regulatory sequences.…”
Section: Discussionsupporting
confidence: 48%
“…37). Thus, VSG ESs are active when transfected as episomes in cells, indicating that several promoters can be active simultaneously (38). This conclusion is also true in procyclic forms, where the ES promoters are normally not active (38).…”
Section: Discussionmentioning
confidence: 51%
“…Several groups have shown that, although VSG mRNAs are not detected in procyclic forms, transcription initiation does occur at a low level from many, if not all, ES promoters (27)(28)(29). This is consistent with the observation of CAT or luciferase expression under the control of VSG gene promoters cloned in episomal vectors in transiently transfected procyclic parasites (29,30). However, when VSG promoters were further analyzed within their chromosomal context, instead of plasmid vectors, it was found that the transcription elongation step is subjected to stage-specific regulation, i.e., the active VSG gene is fully transcribed in bloodstream parasites but most transcriptional activity stops within 1 kb of the VSG promoter in procyclics (27)(28)(29).…”
Section: Smr Teixeirasupporting
confidence: 57%
“…Transient transformation of trypanosomes with foreign DNA (Clayton et al, 1990;Rudenko et al, 1990;Jefferies et al, 1991) or from a T. brucei receptor RNA gene (Rudenko et al, 1991). The neo gene could also be stably expressed without the addition of a promoter element by inserting it into an actively transcribed region, such as the tubulin or calmodulin locus (ten Asbroek et al, 1990;Eid and Sollner-Webb, 1991).…”
Section: Simultaneous Expression Of Luciferase and Neo In T Brucei Bmentioning
confidence: 99%